Towards The Betterment Management And Transparency Of Waqf Institutions: Lessons From The Charity Commission, UK - Hidayatul Ihsan; Abdullah Muhammad Ayedh; Shahul Hameed Hj Mohd Ibrahim (IIUM, 2024)
1st International Forum on Islamic Economics, Finance and Business for Young Scholars, 2006At: Langkawi, Malaysia